2017
DOI: 10.3892/etm.2017.4452
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Mongolian medical warm acupuncture in treating insomnia by regulating miR-101a in rats with insomnia

Abstract: MicroRNAs (miRNAs or miRs) and the target genes before and after warm acupuncture at the genetic level were assessed, and the cytokines and neurotransmitters related to insomnia were studied. Male Sprague-Dawley rats were used to create PCPA insomnia rat models and randomly divided into the normal, model, warm acupuncture, and drug groups. The Dinghui Acupoint, Heyi Acupoint, and Xin Acupoint were inserted in the Mongolian medicine warm acupuncture group. The differential expression profile of microRNA in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…They used parachlorophenylalanine-induced insomnia rat models and performed Mongolian medial warm acupuncture treatment. After the treatment, they detected upregulation of miR-101a in the brain and suggested that the upregulation of miR-101a is probably related to paired box gene 8 regulation [44].…”
Section: Main Textmentioning
confidence: 99%
“…They used parachlorophenylalanine-induced insomnia rat models and performed Mongolian medial warm acupuncture treatment. After the treatment, they detected upregulation of miR-101a in the brain and suggested that the upregulation of miR-101a is probably related to paired box gene 8 regulation [44].…”
Section: Main Textmentioning
confidence: 99%
“…The Mongolian warm acupuncture (WA) is a traditional therapy of Mongolian medicine, which uses silver needles and gives acupuncture and warm stimulation at specified points (Bo et al, 2017). Studies have shown that Mongolian WA can regulate the neuroendocrine and immune system (Huo, 2006;Agula and Chen, 2009;Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The ageing model induced by D-gal has been widely used (21,22) and has been evaluated in behavioral, biochemical and neurochemical aspects (23). The modeling methods of animal models of insomnia mainly include chemical reagent stimulation using intraperitoneal injection of para-chlorophenylalanine (PCPA) (24), the horizontal platform environmental deprivation method (25), the stress stimulation sleep deprivation method (26), the gentle stimulation deprivation method and the forced exercise deprivation method (27). Rat and mouse models can be used; however, rat models are optimal due to model stability in the establishment of the ageing model induced by D-gal (28).…”
Section: Introductionmentioning
confidence: 99%